A permanent magnet hall thruster for pulsed orbit control of lunar polar satellites - Moraes, Brunno Silva; Ferreira, José Leonardo; Ferreira, Ivan Soares; Winter, Othon Cabo [UNESP]; Mourão, Décio Cardozo [UNESP] (IOP Publishing, 2014)
Future Moon missions devoted to Lunar surface remote sensing, for example, will require very fine and accurate orbit control. It is well known that Lunar satellites in polar orbits will suffer a high increase on the eccentricity due to the gravitational perturbation of the Earth. Without proper orbit correction the satellite lifetime will decrease and end up in a collision with the Moon surface. It is pointed out by many authors that this effect is a natural consequence of the Lidov-Kozai resonance. We studied different arcs of active lunar satellite propulsion, centered on the orbit apoapsis or periapsis, in order to be able to introduce a correction of the eccentricity at each cycle. The proposed method is based on an approach intended to keep the orbital eccentricity of the satellite at low values.